Thermosensitive polymer-based hydrogel mixed with the anti-inflammatory agent minocycline induces axonal regeneration in hemisected spinal cord - Kang, Young Mi; Hwang, Dong Hoon; Kim, Byung Gon; Go, Dong Hyun; Park, Ki Dong (Macromolecular research, 2010)
Bridging lesion cavities with bioengineered scaffolds is a promising strategie for spinal cord repair. In a rat model of spinal cord hemisection, the present study utilized an injectable hydrogel Tetronic-oligolactide (TL) copolymer, which is a liquid solution at room temperature and gels at 37 °C. The implantation of the TL hydrogel allowed the growth of laminin-laden connective tissue matrix and the formation of blood vessels in the lesion cavities. However, TL implantation alone did not significantly increase the level of axonal growth through the lesion areas. It was hypothesized that macrophage infiltration into the lesion areas reduced the growth promoting effect of the TL hydrogel. Implanting TL mixed with an anti-inflammatory agent, minocycline, decreased the extent of macrophage infiltration and the deposition of chondroitin sulfate proteoglycans, which can potently inhibit axonal regeneration. Finally, TL plus minocycline increased the length of the axon growth through the lesion areas in a dose-dependent manner. These results suggest that controlling inflammation improves the functionality of an injectable hydrogel used as a bridging strategy.